(untitled) (REVISTA DE AGRICULTURA NEOTROPICAL, 2021)
This study aimed to evaluate the quantitative and qualitative aspects of production in different populations of cotton cultivars. Ten cultivars were evaluated annually in four plant populations. A randomized block design with split plots and three replicates was used. The cultivars were placed in plots, and the plant populations were placed in the subplots. The following characteristics were evaluated: fiber percentage, fiber yield (kg ha-1), fiber length (mm), the micronaire index, the short fiber index (%), and fiber resistance (gf tex-1). In general, the effect of cultivar was much more important than that of the plant population. These results agree with those obtained by several other authors who have claimed that cotton has a high capacity to adapt to certain population ranges. Thus, considering current seed prices, smaller populations can be used without affecting productivity.